Serological characteristics and molecular mechanisms of occult hepatitis B virus infection in blood donors - YU Wei; WANG Fang; LIU Qiang (Zhongguo shuxue zazhi)
[Objective] Abstract: Objective To analyze the serological characteristics of occult hepatitis B virus infection (OBI) in blood donors, and to explore the molecular mechanism of HBV S gene mutation in the immune escape of hepatitis B virus surface antigen (HBsAg). [Methods] From January 2021 to December 2022, a total of 175 583 blood donors were recruited for ELISA/NAT testing. Subsequently, HBV serological marker testing was conducted to confirm the presence of OBI. The HBV S region was amplified using nested PCR and subjected to sequencing analysis. Comparative study was performed using MEGA 7.0 software. [Results] A total of 82 OBI samples were detected, with a detection rate of 0.046% (82/175 583). There was no statistically significant difference in the OBI detection rate among blood donors of different genders (P>0.05). The highest OBI detection rate among blood donors was observed in the age group of 45-54 years, accounting for 39.02%. HBcAb exhibited the highest positive rate at 52.44%. Sequencing analysis of HBV DNA in 12 OBI samples revealed that two cases had genotype B and 10 cases had genotype C. Nested PCR targeting the HBV S region identified amino acid mutations such as T47K, I126S and P127H in all 12 samples. [Conclusion] The implementation of NAT can effectively mitigate or even eliminate the risk of blood transfusion-associated OBI. The presence of high-frequency amino acid mutations, specifically T47K and Q101R, in the C genotype of OBI blood donors may lead to immune evasion, resulting in a negative HBsAg test.